Representações do comer ideal e do comer saudável em pacientes obesos com indicação de cirurgia bariátrica em Goiânia/Goiás - Alves, Larissa de Farias (2016)
As a multidimensional character, eating is inserted into an interstitial space, a system of values specific to each culture, whose complexity and incomprehensibility begin to be understood within the limits of disciplines. Thus, this research uses the perspectives of consumption anthropology, health and disease anthropology and food anthropology to analyze speeches of people assisted in public health services and compare them with current biomedical hegemonic discourses about eating. The methodological strategy was the observational qualitative ethnographic study (participatory) and, as a tool, semi-structured and open interviews were carried out at Clinical Hospital (Goiânia, Goiás) and Family Health Units (Trindade, Goiás). Fundamentally, the research aims to analyze the categories, influence factors, values and meanings involved in the representation of the ideal and/or healthy eating of people who are in a dietary change process under the guidance of nutritionists and who went through some disease process and currently have a biomedical diagnosis of obesity.